Kajian Literatur Penggunaan Media Pembelajaran pada Mata Pelajaran Bahasa Indonesia Berbasis PBL - Eka Sari, Lilis; Ahmadi, Anas (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2024)
This article review aims to collect and review articles that discuss the use of learning media in Problem Based Learning (PBL) based Indonesian language subjects. The research method used is descriptive qualitative with a literature review approach to articles in the last 10 years and obtained 10 articles that meet the requirements. Data collection was done through a literature review of previous articles related to the research. The findings obtained in this study indicate that there are a number of learning media that can be used in Problem Based Learning (PBL) based Indonesian language subjects, namely serialized picture media, wordwall media, animated video media, booklet media, comic media, spinning wheel media, and audio visual media. The conclusion that can be drawn is that these learning media are feasible to use to convey learning materials easily in Problem Based Learning (PBL) based Indonesian language subjects.